Covid-19: Information, Transference, Properties of Human Coronaviruses, and Enhancing Immunity by Dietary Recommendations - Dalia I. Hemdan (Institute of Medico-legal Publications Pvt Ltd, 2021)
In Wuhan City, China was found a new type of viral infection could be a novel CoV strain (2019-nCoV)which as an acute respiratory syndrome CoV-2 (SARS-CoV-2) and formerly, severe acute respiratorysyndrome (SARS). All these emerging infectious diseases are caused great damage to general health.NewCoronavirus has diffused very quickly at the world and the World Health Organization has declared it apandemic. It usually affects people who are immunocompromised. Immunodeficiency often comes fromnutritional deficiency and this makes viruses stronger. Therefore, this review focused on the identification ofthe SARS-CoV-2 virus, its transmission and spread, and the history of Coronavirus. In addition, how to boostimmunity by learn about nutrition recommendations and healthy diets during the COVID-19 pandemic.